1970
DOI: 10.1021/ja00721a001
|View full text |Cite
|
Sign up to set email alerts
|

Fusion properties of some ionic quaternary ammonium compounds

Abstract: Enthalpy, entropy, and molar volume changes during the fusion process of a wide range of quaternary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 4 publications
2
42
0
Order By: Relevance
“…In the liquid state, the sample may reside in the periphery of the crucible due to surface tension. If a ther- [157] 158-159; [158] 164-165; [159] 166 [160] [ mal gradient between the center and the circumference of the crucible exists, slightly different T fus may be obtained. [75] Especially if high melting temperatures are expected, the use of a crucible with an opening is advisable to avoid the influence of pressure.…”
Section: Recommendations For Dsc Measurementsmentioning
confidence: 99%
“…In the liquid state, the sample may reside in the periphery of the crucible due to surface tension. If a ther- [157] 158-159; [158] 164-165; [159] 166 [160] [ mal gradient between the center and the circumference of the crucible exists, slightly different T fus may be obtained. [75] Especially if high melting temperatures are expected, the use of a crucible with an opening is advisable to avoid the influence of pressure.…”
Section: Recommendations For Dsc Measurementsmentioning
confidence: 99%
“…In addition, tetra-nheptylammonium nitrate was investigated to confirm the rather unusual results reported for several other tetrasubstituted salts [5]. The results are listed in the A previous investigation of monosubstituted n-alkylammonium halides showed that the entropies of fusion were less than 5 e.u.…”
mentioning
confidence: 57%
“…However, the existence of several solid-solid transitions in these compounds have been previously established [4][5][6][7]. It would seem that tJ~e crystal and molecular structure of the solid phase existing closest to the melting points (Phase l) should be used as the basis for any comparisons between the solid and molten or solution phases.…”
mentioning
confidence: 99%
“…The uncertainty in density measurements was determined to be 0.00125 g cm -3 . The molarity of solutions was converted to molality using standard expressions [18][19][20][21] and density values. The ultrasonic velocity of solutions were measured with ultrasonic interferometer, model-M-84 (Mittal Enterprises, India,) with a frequency of 2 MHz.…”
Section: Methodsmentioning
confidence: 99%